IMPROVING SOCIAL SENSITIVITY IN SOCIETY WITH INTERNALIZATION VALUE OF MULTICULTURAL EDUCATION - NURDIANSYAH, EDWIN (Sriwijaya University Learning and Education International Conference, 2016)
Humans are social beings so their life will not be separated from community andsocial process. But the negative effects from globalization resulted in some group ofpeople began lose their social sensitivity especially to other community that havedifference of physical, ethnic and cultural. If that problems are not resolved soon itwill be bad for social life because it make people move individualistic and antipathy.Therefore needed an effort to increase the return of social sensitivity in society. Oneeffective way to implement this is through multicultural education. Internalizationvalue of multicultur education at society can create social sensitivity to build caringand good community.